Rethorical models and narrative in “Relação da missão da serra da Ibiapaba”, by father Antonio Vieira - Santos, Fernanda (2019)
Antônio Vieira documents his travels, in the Seventeenth century, through letters (epistolography) and various reports. Among these texts lies "Relação da missão da serra da Ibiapaba”, produced in 1660. This paper  aims at analyzing, in a rhetorical perspective, "Relação da missão da serra da Ibiapaba”, a written report based on the rhetorical precepts of Quintilian’s Institutes of Oratory  and Cicero’s On Oratory, two fundamental works on the subject. The article also observes that this report is a solid component of several other writings about the natives, produced by Antônio Vieira between 1650 and 1660, and in which the rhetorical-argumentative precepts are maintained, in defense of a greater cause: the evangelization of the tabajara natives and the ratification of the presence of the Jesuits in the Ibiapaba mountain range.